Nolla Flooring in Meliana, a jewel of ceramic tiles. Study and cataloguing for its preventive conservation - Aguilar Tamarit, Laura (2022)
The Nolla Mosaic Factory was built by Miguel Nolla Bruget around 1860 on the outskirts of Meliana (Valencia, Spain). Its creation introduced important social, economic and industrial changes in the region. The company earned a place among the top European companies in its area and exported its product both nationally and internationally. It received numerous prizes and medals due to the quality of the ceramic tiles produced, the good working conditions of the operators and the technological innovations that were implemented in the production system. After closing in the 70s of the last century, its importance in the development of the region and the technical and artistic quality of its mosaic tiles were quickly forgotten. This caused the abandonment of the Nolla Palace, the destruction of part of the original facilities of the factory and the loss of a large number of original and unique tiles. Currently, work is underway to recover this heritage and give it the place it deserves. This project makes a small contribution to this goal through the study of the specific case of the Nolla mosaic tiles that are still preserved in Meliana and the creation of a worksheet or its cataloguing.